Research for media production - Chater, Kathy (Media manuals., 2002)
Outlines the main skills, techniques and practices for the job of the researcher. An easy to follow guide to production research, it will help the new researcher to understand the possibilities to be considered when undertaking research and the kind of questions that need to be asked at each stage of the production process. Every project, whether it's a programme for television or radio or an article for publication is different and there is no one, correct answer to each situation. Based on the author's wealth of experience as a researcher on many and varied kinds.